Engaging social media users with corporate social responsibility messages: An integrated theoretical approach in the automotive industry during social media era - He Dong; Pan Zhao; Cindy Sing Bik Ngai (PLoS ONE, 2025)
Corporate Social Responsibility (CSR) messaging on social media has become a key strategy for companies to engage the public. However, limited research has investigated how specific CSR communication strategies influence public online engagement, particularly in the Chinese context. This study analyzed the effects of three dependent variables: (1) CSR message themes (aligned with ISO 26000 standards), (2) relationship cultivation strategies (Openness, Information Dissemination, Interactivity and Involvement, and Sharing Tasks), and (3) multimodal message types (text with emoticons, picutures, and videos) on social media users’ engagement behaviors (likes, shares, and comments). A quantitative content analysis was conducted on 421 CSR-related posts from the Weibo accounts of the top ten automotive brands in China, using Negative Binomial Regression (NB2) to examine the associations between CSR factors and user engagement. The findings revealed that consumer-related CSR themes significantly increased likes, shares, and comments. Relationship cultivation strategies, particularly Interactivity and Involvement, positively impacted engagement, especially in posts that encouraged commenting or sharing. Additionally, posts incorporating text with emoticons were found to significantly boost comments. Theoretically, this study integrates Stimuli-Response Theory’s focus on external stimuli with Uses and Gratifications Theory’s emphasis on users’ active motivations, offering a more comprehensive framework for understanding user engagement. Practically, it provides clear, actionable recommendations for automotive companies: prioritize consumer-focused CSR topics, adopt interactive strategies, simplify technical content, and utilize.